Assessment of Complete Blood Count Parameters for Acute Appendicitis Diagnosis: A Cross-Sectional Study - Mansour Ahmed Ruthan , Hakla Saad Aljameeli , Naif Matar Alanizy , Mona Gharbi AlDhafiri , Marzouq Saad Al-Otaibi , Saeed Ahmed Barji (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background and Aims: Acute appendicitis remain a common cause of abdominal surgeries, presenting diagnostic challenges with a significant rate of negative appendectomy. This study aimed to assess the diagnostic utility of complete blood count (CBC)-associated parameters in distinguishing between positive and negative appendectomy cases. Methods: A cross-sectional study was conducted, including patients suspected of acute appendicitis. Preoperative CBC samples were collected and analyzed for various parameters including white blood cell count (WBC), platelet count (PLT), mean platelet volume (MPV), neutrophils-to-lymphocytes ratio,platelets-to-lymphocytes ratio, red cell distribution width (RDW), and platelet distribution width (PDW). Statistical analysis was employed to compare these parameters between positive and negative appendectomy patients.